A review of crude oil emulsification and multiphase flows in chemical flooding. Issue 4 (24th November 2022) - Zhou, Yazhou; Yin, Daiyin; Li, Yuanting; He, Jingang; Zhang, Chengli
Abstract: Chemical flooding has become an important method to enhance oil recovery in high‐water cut reservoirs. Crude oil emulsification often occurs during chemical flooding, and it plays a very positive role in increasing crude oil production. Crude oil emulsification increases the complexity of fluid flow in the reservoir including multifield coupling characteristics and multiphase flow and multiphase form characteristics. This paper discusses advanced research techniques and the status of multiphase fluid flows in chemical flooding, including the interfacial rheological properties of emulsions, physical simulation of emulsion seepage, and mathematical models and numerical simulations of seepage. Studies on the mechanism of seepage have analyzed the macroscopic and microscopic aspects of seepage during chemical flooding. Prospective directions for future research are indicated including the study of the interfacial rheological characteristics of emulsions, methods for the evaluation of the seepage characteristics of chemical flooding, and mathematical models of multiphase seepage during chemical flooding. Abstract : The multiphase and complex fluid flow characteristics have been investigated in chemical flooding, and the progress of the emulsion rheological characteristics, seepage physical simulation, seepage mathematical model, and numerical simulation have been inspected.